Electronic Structure, Bandgap, and Thermal Quenching of Sr[Mg3SiN4]:Eu2+ in Comparison to Sr[LiAl3N4]:Eu2+. Issue 4 (14th December 2015) - Tolhurst, Thomas M.; Schmiechen, Sebastian; Pust, Philipp; Schmidt, Peter J.; Schnick, Wolfgang; Moewes, Alexander
Abstract : In this study the band gap and electronic structure of the next‐generation, red phosphor Sr[Mg3 SiN4 ]:Eu 2+ (SMS) are explored through a combination of soft X‐ray spectroscopy, density functional theory calculations, and thermal quenching data for the Eu 2+ 5d→4f emissions. The results will be compared to those for the high‐efficiency phosphor Sr[LiAl3 N4 ]:Eu 2+ (SLA), which shows different, yet exceptional emission characteristics in the red‐spectral region. It is found that SMS has an indirect band gap of 3.28 ± 0.20 eV, strong uniformity in the density of states of its nonequivalent nitrogen sites, and an estimated energetic separation between the lowest Eu 2+ 5d state and the conduction band of ≈0.13 eV. The Eu 2+ 5d–conduction band separation in SLA is found to be ≈0.28 eV, which points to why the visible emissions of SLA, and not SMS, show outstanding thermal stability. A bonding scheme explaining the band gap difference of SMS and SLA is proposed based on the density of states of SMS. Modifications to each lattice are put forward for achieving optimized phosphor characteristics for use in pc‐LEDs. Abstract : The electronic structure of the luminescent material Sr[Mg3 SiN4 ]:Eu 2+ and its relation to this material's exceptional emission characteristics in the red‐spectral region is presented. The comparison is also made to another red‐emitting material, Sr[LiAl3 N4 ]:Eu 2+, giving insight into to tune the band gap and emission properties of these luminescent materials.